(untitled) (INNOVATIVE ECONOMY, 2020)
Paliukh M.S., Bryk M.M. FEATURES OF THE ACCOUNTING OF BIOLOGICAL ASSETS TAKING INTO ACCOUNT INTERNATIONAL STANDARDS Purpose. The aim of the article is to study trends in the peculiarities of accounting for biological assets taking into account international standards. Methodology of research. General scientific and special methods are used in the process of research, in particular: the analytical method is used in the review of regulatory and legal sources; the classification method has made it possible to differentiate the main components of accounting for biological assets, and the description method gives them a detailed description; the monographic method is used in the study of literary sources on accounting for biological assets; the system and analytical method is used in processing the received information. Findings. Approaches to the definition of the essence of biological assets are considered, their features are determined, identification characteristics and importance for economic activity are substantiated. The classification and classification of biological assets in accordance with the needs of management is generalized and improved. Problems of the development of accounting of biological assets have been identified, and the author’s vision of their solution is proposed. The essence of the concept of accounting for biological assets is specified. The approach to the estimation of the object of accounting is proposed, ways of determining the estimation of biological assets accounting are substantiated. Approaches to fair value estimation are considered: market, income, expense. Originality. The methodology for assessing objects of biological assets accounting, as well as proposals for its implementation, was further developed. Proposals for the improvement of methodological principles and organization of accounting of biological assets have been developed. The proposals on the improvement of methodological approaches for estimating biological assets at fair value are formulated. Practical value. The obtained results of the research can be used by business entities in the agrarian business in the process of accounting for biological assets and their evaluation according to different criteria. Key words: accounting, biological asset, long-term biological assets, current biological assets, standard, assessment.